An Empirical Investigation of Nutrition and Health Claims in Shaping Consumer Pre-Purchase Intentions - Kashif, Shumaila; Rashidi, Muhammad Zaki (JISR management and social sciences & economics, 2013)
Due to increase in adverse effects of changing lifestyle all around the globe, health consciousness is increasing among people resultantly the belief that healthy food intake is better than using medicine has given rise to the development and marketing of healthy packaged food products commonly known as functional food. The purpose of this research is to investigate consumer’s attitude towards nutrition and health claims products and their pre-purchase intentions. The aim is to analyze underlying motivations which form the basis of attitudes viz. health consciousness, health benefits and health beliefs. This research is an empirical investigation, conducted through a quantitative survey by selecting 500 respondents from three different supermarkets in Karachi. Correlation and regression analyses are used to find out the relationship among the variable and ANOVA is employed to evaluate the moderating effect of socio-demographic variables on pre-purchase intentions. Five in-depth interviews and two focus groups are also conducted to develop an understanding on consumers’ beliefs towards these claims. The results reveal that health consciousness, health benefits and health beliefs explain variation in attitude towards nutrition and health claim products and prepurchase intentions. Also, they are significantly correlated with each other except health belief. Significant effect of various socio-demographic variables are found such as married, young and educated females are more concerned about health and have high pre-purchase intentions as compared to the other groups. However, income does not affect other variables but influences purchase intentions among all age groups. The results provide insight to local healthy food products market, and food marketers may take expert opinion of nutritionists to endorse their products as, generally, respondents are skeptical about the claims. Also, claims should be communicated in a clear, comprehensible and less scientific way to increase consumer response to these products.